Anti-inflammatory effect of Ficus Deltoidea jack extract in behavioral and cellular models of depression - Wang, Huiling (2017)
Depression, a worldwide mental disease, brings an enormous burden to the patients and their families. Current treatments for depression are far from satisfactory. It is required to develop the novel antidepressants from the natural medicines which are good antidepressants with less side effects. Many hypotheses have been put forward to clarify the origins of depression. The inflammatory hypothesis points to the significant role of psychoneuroimmunological dysfunctions. Anti-inflammatory therapy is receiving closer attention. Ficus deltoidea (FD) is one of the well-known traditional medicinal plants in Malaysia. Phenolics and flavonoids are the major components responsible for its antioxidant and anti-inflammatory effects. The present study was carried out to investigate the antidepressant-like effect and the anti-inflammatory properties of FD extract by in vivo and in vitro method respectively. In vivo antidepressant-like potential of FD extract was evaluated by the alterations of body weight and behaviors induced by chronic unpredictable mild stress (CUMS). Oral administration of FD significantly ameliorated the decreased body weight and depressant-like behaviors induced by CUMS which included reduced sugar intake, decreased score of open field test (OFT), and increased immobility time in forced swimming test (FST). FD administration also decreased the amount of pyknotic and dark stained hippocampal neurons of depressed rats. In vitro anti-inflammatory effects of FD extract were assessed by the production of inflammatory mediators and the changes of morphology which were induced by lipopolysaccharide (LPS) in BV2 cell line. FD pretreatment showed significant inhibitory effects on the release of nitric oxide (NO) and tumour necrosis factor (TNF)-α, the expression of inducible nitric oxide synthase (iNOS) and CD40 from LPS-activated BV2 cells. FD pretreatment also attenuated the morphological changes of microglia induced by LPS. FD-pretreated conditioned medium was transferred from BV2 cells to N2A cells. It was proved through immunocytochemical staining and MTS assay that FD-pretreated conditioned medium decreased the neuronal damage induced by LPS. The above results suggest that FD treatment ameliorates the behavioral alterations induced by CUMS, significantly inhibits LPS-induced microglia activation and the release of inflammatory mediators and possesses neuroprotective effects. The mechanism of antidepressant-like activity of FD may therefore be due to its anti-inflammatory and neuroprotective property.